ANALYSIS OF IMPLEMENTATION OF COURT DECISIONS ON CUSTOMARY LAND DISPUTES IN INDONESIA - Rijal, Nur; Fuad, Fokky; Rifai, Anis (UNES Law Review, 2023)
Customary land is one of the sources of agrarian conflicts that often occur in Indonesia. The government has attempted to resolve land disputes by involving the judiciary. However, the implementation of court decisions often does not meet the expectations of indigenous peoples, so the conflict continues. This study aims to analyze the implementation of court decisions on customary land claims in Indonesia. The method used is normative legal research with a case approach. This study uses secondary data from court decisions and related documents. The results of the research show that the implementation of court decisions on customary land disputes in Indonesia still faces various obstacles. Some of these obstacles include the ignorance of indigenous peoples about court decisions, the slow execution of decisions, and the lack of support from the government in enforcing court decisions. This study recommends the need for efforts to increase awareness of indigenous peoples regarding court decisions, accelerate the execution of decisions, and increase support from the government in enforcing court decisions. In addition, there is a need to formulate clear and firm regulations regarding the implementation of court decisions on customary land disputes in Indonesia.